Chatter stability of the constrained layer damping composite boring bar in cutting process. (August 2019) - Yuhuan, Zhang; Yongsheng, Ren; jishuang, Tian; jingmin, Ma
Traditional boring bars are generally made up of isotropic metallic materials and exhibit extremely poor chatter suppression ability. For enhancing the chatter stability, using anisotropic composite materials in the preparation of boring bars proves to be an effective method so as to enhance the boring bar's natural frequency and damping. Additionally, the addition of constrained layer damping (CLD) technology on the composite boring bar can further improve the damping performance. This study aims to develop a theoretical analysis model for the prediction of the chatter stability of the CLD composite boring bar and explore the effectiveness and practicability of the CLD technology in suppressing the chatter of composite boring bar. Based on Euler–Bernoulli beam theory and the complex stiffness method of CLD, the structural dynamic model of the CLD composite boring bar was derived, and some structural parameters of the bar mainly including the ply angle of the composite material, the thicknesses of both damping layer, and constrained layer were also optimized. By combining the linear model of cutting force with a regenerative delay effect and the established dynamic model, the chatter analysis model of the CLD composite boring bar was constructed and the lobe diagram of the chatter stability of the cutting system was plotted by means of frequency domain method. The effects of the ply angle of the composite boring bar, the thicknesses of damping layer, and constrained layer on the chatter stability were examined. By performing time integral of the delay equation of motion, the time-domain response curves of the cutting system are obtained. The chatter stability prediction results based on the lobe diagram fit well with the prediction results on the basis of dynamic stiffness calculation and time-domain numerical integral results.